Expanding Ezekiel the hermeneutics of scribal addition in the ancient text witnesses of the book of Ezekiel - Mackie, Timothy P. ([s.l.] Vandenhoeck Ruprecht, 2015)
Timothy P. Mackie is adjunct Professor of Old Testament and Hebrew at the Western Seminary, Portland, Oregon.
Biographische InformationenTimothy P. Mackie is adjunct Professor of Old Testament and Hebrew at the Western Seminary, Portland, Oregon. ReiheForschungen zur Religion und Literatur des Alten und Neuen Testaments - Band 257
2. Scribal Expansion in Other Literary Traditions3. The Scope of Scribal Expansion in Ezekiel; 4. Coordinating Scribal Additions and the Emerging Scriptural Collection; Appendices; Appendix I: Index of Scribal Additions; Appendix II: Categorized List of Scribal Additions; Bibliography; Index of Authors; Index of Topics; Index of Biblical References
Description based upon print version of record
Keywords: Bibel; Electronic books; Hochschulschrift